Efecto del porcentaje molar de mg y temperatura de recocido sobre el tamaño de grano y conductividad eléctrica en el dopaje de películas semiconductoras de zno por el método sol-gel - Alva Deza, Karina María (2018)
In the present research, thin films of magnesium doped ZnO were elaborated at a concentration of 0.65 M, which were synthesized using the sol - gel method deposited on quartz substrates of dimensions 11mm x 11mm x 2mm by spin - coating. It was possible to evaluate the influence of the effect of the annealing temperature (400, 500 and 600 ° C) and the molar percentage of the dopant (2, 4, 6 and 8%) on the electrical (conductivity) and morphological properties specifically the grain size. It was found that the thin films of ZnO show the best electrical conductivity doped at 2% Mg and without doping 0% Mg being (8.55 and 8.77) 10-7Ω-1cm-1 respectively at an annealing temperature of 600 ° C and the lowest electrical conductivity is given to a doping of 8% Mg with a value of 1.48 x 10-7Ω-1cm-1 at an annealing temperature of 400° C, thus determining that the Conductivity is inversely proportional to the concentration of magnesium and directly proportional to temperature, this electrical property was measured by the four-point method of Lord Kelvin. It was also found that the greater grain size of the ZnO films were given at a doping of 2% Mg and without doping 0% Mg with values of 38.56 and 40.10 nm respectively at an annealing temperature of 600 ° C and the smaller grain size was given for a doping of 8% at an annealing temperature of 400 ° C being 14.13 nm, so that the grain size grows as the temperature increases, but decreases as the molar Mg concentration increases, the grain size was determined by the Scherrer equation for the plane (002) that was found when performing XRD, the results of this technique also showed that all the thin ZnO films doped with Mg have a wurtzite hexagonal structure with an orientation preferential to the plane (002). Further, an optical property such as transmittance with the UV-visible spectroscopy technique was evaluated to determine the existence of zinc oxide and the width of the "band gap" of the thin films of ZnO by the tangent method where it was observed that the band gap increases with increasing Mg concentration, but decreases with increasing annealing temperature.